Elderly health care in Primary Care: a literature review (Research, Society and Development, 2022)
Objective: This study aims to evaluate, according to recent literature, the assistance provided by the health system to elderly patients in Primary Care. Methods: This is an integrative review study, where the databases Periodicals Capes, Scientific Electronic Library Online (SciELO), Latin American and Caribbean Literature on Health Sciences (LILACS) and Library Virtual Health (VHL). The inclusion criteria were primary articles, with abstracts available online, full text available in the selected databases, articles published in the years 2017 to 2022, in Portuguese and that addressed the aforementioned topic. Final considerations: The study highlighted the need for greater care given to the elderly in the face of health problems and physiological changes relevant to aging, which indicates the need for health interventions not only to treat diseases, but also to promote quality of life.